DISPARITAS PEMBANGUNAN ANTAR DAERAH - Sugama, Fiji (Jurnal Ilmu Administrasi Negara, 2016)
Between Regional Development Disparities. The purpose of this study was to analyze the conditions of development disparity and the factors that most influence the development disparity between the Regency/City in Riau Province, as well as to analyze the correlation between the disparities of development and prosperity. The research method uses quantitative and qualitative approaches. Data used is secondary data obtained from the Central Bureau of Statistics and agencies associated with this research. Data were analyzed using multiple linear regression. After doing research, it was found that the value of the index development gaps between regions in Riau province is at a high level. Factors that most influence on the development disparity between the Regency/City in Riau Province is the Human Development Index. The disparity between the development and welfare of the community there is a causal relationship, as well as the correlations between them are positive.